Computerized and distance learning systems (the case of medical diagnostics) - B. A. Kobrinsky (Открытое образование (Москва), 2018)
The purpose of this paper is to analyze the current state and the possibility of developing computer systems of various types in education (the case of medicine). Particular emphasis is on the use of case studies that combine linguistic and multimedia components and on intellectual technologies to implement the learning process, individually controlled at different stages. The considered methods of knowledge engineering in the construction of intelligent systems form the skills of individual and teamwork. A separate aspect is the methods and means of distance learning with the use of telemedical and internet technologies in teaching and continuous professional development. Ontologies are used as a means of cognitive visual representation of knowledge. They find application in the presentation of medical knowledge that characterize pathological processes. Intellectual maps and concept maps are used as the primary analysis of logical relationships of characteristics. Role games contribute to the development of knowledge extraction for expert systems. This allows all members of the group to simulate the roles of a knowledge engineer and an expert. In addition, the teacher corrects, if necessary, this process and indicates in conclusion on the mistakes made and the unused possibilities for optimizing the dialogue between the student-cognitive scientist and the student-expert. Based on case-method it is proposed to implement examples and questions from clinical practice, including video fragments. This allows you to monitor the correctness of the actions of students during inspections and manipulations. The expert system and remote methods of work are used for the analysis of microscopic drugs under the supervision of the teacher. Building an intellectual learning system that includes cases is the basis for acquiring the skills of differential diagnosis in the process of examining a virtual patient. Telemedical technologies, using different video cameras, suggest remote teaching of not only theoretical, but also clinical subjects with examination of patients, including testing of students and video examinations.As a result of the research, the author proposed schemes of computerized and intellectualized technology for teaching medical subjects of various types (morphological, clinical, and cybernetic). This contributes to the increase of knowledge, taking into account the individual abilities of students on personal programs, forms skills to extract and analyze the information received. Videoconferencing allows you to improve your skills remotely at the place of work in the process of contact with lecturers and teachers. Specially developed approaches presuppose remote examination and diagnostics under the supervision of the teacher. In addition, demonstration of patients with various pathologies during telelectures. These approaches offer opportunities for individual mastering of knowledge based on modern methods of electronic education and intellectual technologies. Personalization of the approach to learning allows you to repeat the insufficiently mastered sections of the material. Distance learning methods will allow setting and solving tasks of continuous improvement of professional skill of medical workers on a fundamentally new level. In principle, the use of many of these approaches is possible in other areas of education.